Perceived Adequacy of Tangible Support during Stay-at-Home Orders in Chicago and New York. (June 2021) - O'Conor, Rachel; Opsasnick, Lauren; Pack, Allison; Yoshino Benavente, Julia; Curtis, Laura M.; Lovett, Rebecca M.; Luu, Han; Wismer, Guisselle; Kwasny, Mary J.; Federman, Alex D.; Bailey, Stacy C.; Wolf, Michael S.
Objectives: Physical distancing precautions during the COVID-19 pandemic may challenge the provision of tangible support many middle age and older adults receive in managing their health. We examined the association between unmet tangible support needs and self-management behaviors and mental health status during the stay-at-home orders in Chicago and New York. Methods: We used data from the COVID-19 & Chronic Conditions study collected between May 1st and May 22nd, 2020. A total of 801 middle age and older adults with ≥1 chronic condition in Chicago and New York City completed the telephone interview. Adequacy of tangible social support was measured using a brief, validated scale that determined whether an individual needed assistance managing his or her health, and if yes, whether this need was met. Participants reported their level of difficulty engaging in self-management behaviors using 2 discrete items; they also self-reported medication adherence using the ASK-12 medication adherence scale. Mental health status was measured using the depression and anxiety PROMIS short-form instruments. Results: Participants' mean age was 63 years; 30% identified as Black, 26% identified as Latino, and 12% identified unmet support needs. Inadequacy of tangible support was associated with greater difficulty managing one's health and accessing medications due to COVID-19, as well as poorer medication adherence, increased anxiety and depressive symptoms, and poorer overall well-being ( P 's < .05). Conclusions: Perceived unmet support needs during stay-at-home orders were associated with greater difficulty engaging in self-management behaviors and poorer overall well-being. Two brief items quickly identified individuals with unmet support needs.